Percepção do mercado romântico e influência do contexto nas preferências românticas entre universitários - Castro, Felipe Nalon (2013)
Men and women express different preferences for ideal romantic partners. These preferences seem to vary with the level of involvement and commitment expected for the relationship and the perceptions people have about themselves. The current work was developed to expand the findings related to this subject, investigating the market perception of romantic relationships and the effect of context on self-assessment and preferences for romantic partners. For this purpose, 753 undergraduate, Brazilian and American, were enrolled between March 2010 and November 2012 and took part in at least one of the four studies that compose this research, performing the assessment of specific stimulus-subject descriptions. Studies one and two addressed Brazilian and American samples to respectively describe female and male expectations on human mating market. It was observed that individuals from both the genders expect positive assortative mating within couples, that each trait is not evaluated independently, and, in addition to biological predispositions, factors as environmental local constrains and cultural values may also affect mating expectations. The contrasts between the samples showed that Americans valued physical-attractiveness and social-status in describing the same-gender subjects and their expected partners, while Brazilians valued social-skills. Another expectation was also identified for both genders: physically attractive women and men of high-status were expected to be paired to each other. Study three addressed males and females expectations regarding which characteristics are most relevant in ensuring desirable partnerships for same-gender individuals. The results showed that men and women can be grouped together by having similar expectations. However, the group mainly composed of men considered status characteristics as the most important attributes, while the groups mostly composed of women indicated that social skills or physical characteristics as the most important in appealing to a desirable partner. Finally, study four investigated the effect of social comparison on self-perception and mate preferences, revealing that individuals were aware of the attributes valued by the opposite-gender and that self-perception was affected by the attributes of other people. In sum, this work evidenced that romantic relationships can be interpreted as a biological market and that the value of the attributes in the romantic mating marketplace are associated with reproductive relevance of the characteristics.